Evaluasi lanskap daya tarik wisata pantai di Kecamatan Kuta dengan metode Coastal Scenic Evaluation System (CSES) - Ni Putu Krisnanda Mahaswari; Lury Sevita Yusiana (Prodi Arsitektur Lanskap, Fakultas Pertanian, Universitas Udayana, 2025)
One of the tourism areas renowned for its coastal tourism is Bali. The main attraction of Bali is its natural beauty, with the most popular natural tourist attractions being beaches/oceans. Many favorite tourist spots are found in Kuta. Tourism development tends to focus on the construction and development of tourist attractions without paying much attention to the sustainability of the attractions themselves. The purpose of this study is to determine the quality landscape in the beach area of Kuta District and provide landscape development recommendations to improve its quality. This study focused on finding recommendations that can be implemented to preserve the natural attractions present on the beach. The method used in this study is a descriptive method with a quantitative approach, utilizing observation and literature studies for data collection. Data were obtained through observations and processed using the ‘CSES 2018 V1’ program. The research results show that the five beaches in Kuta District, such as Seminyak Beach (D = -0.65), Legian Beach (D = -0.66), Kuta Beach (D = -0.66), Kelan Beach (D = -0.80), and Kedonganan Beach (D = -1.05), have highly similar landscape characteristics. Based on the classification of D values using the CSES method, these five beaches fall into Class V beaches (D < 0.00), which are described as highly unattractive urban areas.